THE CHAOTIC AGRICULTURAL PRODUCTION GROWTH MODEL: THE DANUBE COUNTRIES - Јаблановић, Весна Д. (Economics of Agriculture, 2011)
The ten Danube countries are : Germany, Austria, Slovakia, Hungary, Croatia, Serbia, Bulgaria, Moldova, Ukraine and Romania. The Danube countries are facing several challenges: environmental threats, insuffcient transport and energy connections, uncoordinated economy, education, research. Also, it is important to improve security system in the Danube countries. The basic aims of this paper are: frstly, to set up a chaotic agricultural production growth model , that is capable of generating stable equilibria, cycles, or chaos, and secondly, to analyze the local stability of agricultural production growth in the Danube countries in the period 1961-2009 . The estimated model confrms the local stability of agricultural production growth in the Danube countries in the observed period.